Diseño de un proyecto agroecoturístico en la hacienda "Salvatierra" ubicada en la comuna sacachún, provincia de Santa Elena, año 2020 - Molina Moran, Yahaira Alejandra (2020)
The objective of the following research to propose the design of an agroecotourism project in the Salvatierra farm located in the Sacachun commune, Santa Elena province, year 2020, where a situational diagnosis was made, collecting necessary information through field visits to verify the natural resources it possesses thanks to its privileged geographic location such as scenic beauty, endemic flora and fauna, as well as a rich climate and soil for crops and crops, being attributes that are favorable for being a tourist power. Surveys were also carried out on 267 inhabitants of the Santa Elena canton, which allowed determining their degree of knowledge about the agroecotourism activity and acceptance of it, giving rise that 76% do not know about the farm, but in tum they would like to have experiences within it, these as leaming, rest and recreation, allocating more than one day to the visit, as well as 85% agree that this modality would generate direct employment for the residents who reside in neighboring communes. Finally, with the appropriate management model, it allows to have a coordinated an administration through programs, projects, strategic plans aimed at hacienda tourism, being an example to follow for those who wish to lean towards this new modality, thus promoting that more haciendas and farms are visited. Although it is true, it is a little known activity but it is on the rise, which is of great contribution to make our Ecuador a leading country with sustainable tourism Keywords: design, agroecotourism, management model, agroecotourism farm